Exploring Superiority and Racism as the Impacts of Paternalism in Burmese Days by George Orwell - Adi, Bagas Cahyo; Istiani, Imas (Pioneer: Journal of Language and Literature, 2024)
Burmese Days is a novel by George Orwell, inspired by his experiences as a police officer in Burma. At that time, Burma was under British colonial rule, which led to the belief that local people were inferior to British people. This research aims to show how George Orwell depicts one of the characters, Ellis, with a sense of superiority and racism based on paternalism. The research uses a qualitative descriptive method, using Edward Said’s theory of Orientalism as the primary source to understand how the West defines the East. Orientalism is a way to understand the East based on the experiences and knowledge of Europeans. This research aims to discover the sense of paternalism in the novel and how paternalism caused racism and superiority. The researchers found that the arrival of the British to Burmese made Ellis think that local people could not govern themselves. He felt that local people were destined to be enslaved, and this sense of colonialist paternalism caused racism and superiority to emerge in him. Ellis firmly refused to accept local people into the club by raising the issue of racism and the superiority of British people over local people.